Transmission of transgenic mosquito-killing fungi during copulation - Etienne Bilgo; Brian Lovett; Abel Souro Millogo; Issiaka Sare; Edounou Jacques Gnambani; Raymond St. Leger; Abdoulaye Diabaté (Scientific Reports)
Abstract Entomopathogenic fungi engineered to express insect-specific neurotoxins have demonstrated potential as microbial control agents against malaria mosquitoes. Currently, the primary application method is via direct contact of spores with indoor resting mosquitoes. However, many malaria-transmitting mosquitoes feed and rest outdoors. To target these, we have developed an alternative application method that exploits the lethality of transgenic fungi as a sexually transmitted mosquito disease. This approach has both a wider interdisciplinary significance and important implications for preventing mosquito-borne diseases.